Analiza czynnikowa zmiennych porządkowych - Sztemberg-Lewandowska, Mirosława (Factor Analysis For Ordered Categorical Variables, 2007)
The method of factor analysis is widely used as an exploratory tool to reduce the dimensionality of multivariate data. The fact that the standard model is strictly applicable only when the manifest variables are scaled is a serious limitation in economic science where the variables are often categorical. The classical factor analysis is based at Pearson correlation, while factor analysis for ordered variables uses polychoric correlation or tetrachoric for binary data. The article presents the usage of factor analysis to reduce the set of coffee characteristics in order to reach the few major factors influencing consumers' choice of a brand.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 489-498